Topical estrogens combined with argon plasma coagulation in the management of epistaxis in hereditary hemorrhagic telangiectasia - Bergler, Wolfgang; Sadick, Haneen; Riedel, Frank; Götte, Karl; Hörmann, Karl (Annals of otology, rhinology & laryngology, 2002)
The aim of this study was to assess the value of topically applied estrogens in patients with hereditary hemorrhagic telangiectasia. Twenty-six patients with this disorder were treated with argon plasma coagulation and randomized into 2 groups: group A, which had postoperative application of estriol ointment (n = 14), and group B, which had postoperative application of dexpanthenol ointment (n = 12). Over a period of 12 months, the frequency and intensity of bleeding, the patient's satisfaction, and the success of the treatment were evaluated with a questionnaire. Before the operation, more than 90% of the patients in both groups complained of daily episodes of epistaxis. Twelve months after treatment, the frequency and intensity of bleeding had significantly decreased in group A as compared to group B. Of the patients in group A, 93% were satisfied with the treatment. Of the patients in group B, only 42% were satisfied with the treatment. In both groups, more than 90% of the patients were willing to undergo the same treatment again. The combined treatment approach with argon plasma coagulation and topical estriol enables us to significantly prolong the hemorrhage-free interval.
Gesehen am 06.05.2022